Implementasi Model Pembelajaran Teams Games Tournament di SD Margorejo 01 Kecamatan Pati - Luqmani Rohmad Maghrib; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
This study aims to develop students' understanding of events, facts, concepts and generalizations related to real life. The Teams Game Tournament model is a learning model that includes activities for all students regardless of position, includes the role of students as peers, and includes elements of play and reinforcement. The Teams Game Tournament learning model is expected to provide improvement and enhancement of learning. Based on the results of research conducted in Class V SD Negeri Margorejo 01 Pati, it can be concluded that the Teams Game Tournament learning model can improve teacher skills, student learning outcomes in the cognitive, affective, and psychomotor fields in learning Citizenship Education on freedom of association.